D-Dimer and Brixia Score to Mortality in COVID-19 Patients - Falyani, Silvy Amalia; Pratiwi, Suryanti Dwi; Setyawan, Ungky Agus; Erawati, Dini Rachma; Djajalaksana, Susanthy; Listyoko, Aditya Sri (Jurnal Respirasi, 2024)
Introduction: Coronavirus disease 2019 (COVID-19) is a highly contagious severe and acute respiratory syndrome caused by the SARS-CoV-2 virus. A variety of factors can increase a patient's risk of death, including coagulopathy characterized by increased D-dimer levels. Brixia scores could be one of the determinants of COVID-19 severity, as assessed by chest radiographs. This study aimed to analyze chest radiographic severity based on the Brixia score at the degree of coagulation based on D-dimer in mortality of COVID-19 patients who were hospitalized. Methods: This cohort retrospective study was conducted at Dr. Saiful Anwar General Hospital, Malang, using an observational cross-sectional design. The study included 300 medical records of COVID-19 patients who passed away while hospitalized. The data were analyzed using the Wilcoxon test, and the results were also tested for Spearman correlation to determine the relationship between variables. Results: Significance results of median D-dimer were found by age and severity of COVID-19 (p-values 0.015 and 0.002), and median Brixia scores by age, gender, severity of COVID-19, and length of treatment (p-values 0.001, 0.001, 0.001, and 0.005). The results were also compared with normal values, which were significant (p = 0.000). Spearman correlation test results between the final D-dimer and the initial Brixia score (p = 0.005). Conclusion: The research results display a retrospective study of the correlation between D-dimer and Brixia score values "‹"‹and outcomes in COVID-19 patients. Higher D-dimer values"‹ "‹and Brixia scores on admission were shown to be associated with mortality.